2009
DOI: 10.1002/14651858.cd006422.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial interventions for the prevention of disability following traumatic physical injury

Abstract: This review provides no convincing evidence of the effectiveness of psychosocial interventions for the prevention of disability following traumatic physical injury. Taken together, our findings cannot be considered as supporting the provision of psychosocial interventions to prevent aspects of disability arising from physical injury. However, these conclusions are based on a small number of disparate trials with small to moderate sample sizes and are therefore necessarily cautious. More research, using larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 76 publications
(44 reference statements)
0
25
0
Order By: Relevance
“…PTSD symptoms include intrusions of the traumatic event, avoidance of stimuli related to the event, emotional numbness, and hyperarousal [6]. Until now, efforts to prevent PTSD onset, for example, psychological debriefing, have been unsuccessful [7,8]. Early treatment of PTSD, or its precursor Acute Stress Disorder, with 4-5 sessions of trauma-focused cognitive behavioral therapy (CBT) was found to be effective in preventing chronic PTSD [9].…”
Section: Introductionmentioning
confidence: 99%
“…PTSD symptoms include intrusions of the traumatic event, avoidance of stimuli related to the event, emotional numbness, and hyperarousal [6]. Until now, efforts to prevent PTSD onset, for example, psychological debriefing, have been unsuccessful [7,8]. Early treatment of PTSD, or its precursor Acute Stress Disorder, with 4-5 sessions of trauma-focused cognitive behavioral therapy (CBT) was found to be effective in preventing chronic PTSD [9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent Cochrane review found some evidence that identifying, targeting and monitoring patients at risk of poor outcome following a traumatic injury may reduce secondary disability. 12 The primary limitation of this study was in participant numbers. Higher numbers would have enabled the study to analyse outcomes based on different premorbid conditions.…”
Section: Discussionmentioning
confidence: 98%
“…This has been the subject of a Cochrane review. 12 Quantifying how the trauma itself may contribute to poorer outcomes may be harder to do. The use of simple tools such as the SF12, 13 a quick survey designed to assess mental and physical functioning, could give an early indication of those at risk of psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Although all these ideas to help keep people healthy and employed are presented in the literature, little, if any, large-scale research has tested the effectiveness of these approaches to preventing disability. A few studies have tested strategies to prevent disability in specific populations (e.g., the frail elderly [9], people with back pain [5], individuals with traumatic injury [2], or people who have already had a medical-related work absence [15]); however, no studies to date have evaluated programs to prevent disability among currently working individuals with a wide spectrum of chronic mental and physical conditions.…”
Section: Preventing Disabilitymentioning
confidence: 99%